The Procusto bed and the archival records classification schemes: analysis of the archival records classification code: administrative activities of the National Archives - Sousa, Renato Tarcisio Barbosa de (2021)
The topic of the article is the classification of records, as part of representation and organization studies, and, more specifically, record classification scheme. The schemes for classifying records are prepared mixing several classification principles in the same classificatory structure. This form gives rise to schemes that are difficult to understand by the user, and do not favor retrieval, the maintenance of the archival bond, and the substantiation of other archival functions. The research question was: is the new version of the record classification code consistent from the standpoint of structure, logic, and semantics? The objective was to verify whether the new version of the classification code, released by the Portaria do Arquivo Nacional nº. 47/2020, has the structural, logical and semantic elements that favor its understanding and its application. The research, as to its objective, is of the exploratory type, as it seeks to broaden knowledge about a theme, the record classification scheme, little explored by the area. It is a bibliographic and documental research as far as the collection procedures and the sources of information are concerned. And it is a qualitative research regarding the nature of the data. It is also a documental research, because it works with the analysis of the classification scheme prepared by the National Archive and the material produced by the Brazilian archival institution to facilitate the understanding and the methodology used in the instrument. It was noticed that the new version presents several advances in relation to structure, logic and semantics.